MODIFIKASI BAN MOTIF ALUR RIB SEGITIGA UNTUK MENINGKATKAN KESELAMATAN BERKENDARAAN SEPEDA MOTOR - Wahyu Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2010)
The tire has an important role in transport because they have a lot of functions and duties such as to sustain the burden of holding the entire vehicle, at full load and empty load when stopped or running. Therefore, tire must be inspected at any time to know the condition of tires fit or not. Vehicle tires basically have two types: Bias tire / diagonal consists of outer and inner tube tire and inner tube type without tire (tubeles). The model of many both bias tires and radial tires is motives groove / trench and the soles of rib. Basically, rib tire tread motif has two kinds: the transverse groove motif and motif longitudinal groove, but along with the development of manufacturing technology, palm motif groove / rib tires combine or modify them. Nowdays, rib tire tread motif modification has made oblique, straight italic, straight across the curve and combination. With a variety of motives model rib tire now, in this article I introduced a new model tire rib motif with the patterns of rib tire model/ triangular groove profile tire designed circular shape on the sides of tire edge. The purpose of the triangle rib model is to provide the tires grip the road surface, particularly when bikers turn with a certain tilt angle. It is very influenced by the speed of the motorcycle itself on the road when turning, but bikers are expected to keep stable speed and controlled